SYNTHESIS, CHARACTERIZATION, DNA BINDING AND CLEAVAGE STUDIES OF Fe(III) AND Zn(II) COMPLEXES CONTAINING MIXED LIGANDS - B.SREEKANTH; G.KRISHNAMURTHY; H.S.BHOJYANAIK; S.M.GOPINATH; T.K.VISHNUVARDHAN; M.ISMAIL SHAREEF (International Journal of Pharma and Bio Sciences, 2013)
The newly synthesized mixed complexes of the type [Fe(L1L2L3)] (PF6)3 complex (1), [Zn(L1L2L3)] (PF6)2 complex (2), (where L1 = 1, 10-phenanthroline and L2 = 1H-benzimidazole-2-thiol and L3 = 4H-1,2,4-triazol-4-amine) were characterized by elemental analysis IR, UV and NMR spectral studies.The DNA interactions of complex (1) and complex (2) was determined by absorption spectral studies. The results of binding constant indicate that all the complexes intercalate with CT-DNA. The relative nuclease activity of these complexes were studied by gel electrophoresis using pUC 19 DNA.